Stage III Colon Cancer: The Individualized Strategy of Adjuvant Chemotherapy for Aged Under and Over 70. - Chieh-Sheng Lu (PLoS ONE, 2015)
The aim of this study was to examine the specific chemoregimens selected for adjuvant therapy in the patients with stage III colon cancer. We investigated the trends in chemotherapeutic prescribing patterns and looked for adequate therapeutic setting for these patients.288 patients presenting with stage III colon cancer and undergoing adjuvant therapies after curative surgery for more than 3-month were enrolled between January 2006 and December 2011. Demographic characteristics and therapeutic factors were analyzed, including age, gender, histological grade, tumor sizes, tumor location, pathologic stage, performance status, serum carcinoembryonic antigen, regimens selection, interval from the operation to the start of adjuvant therapy and prolonged adjuvant therapy. Kaplan- Meier methods were utilized for drawing survival curves and Cox model was used to analyze survival, prognostic factors.The analysis showed that the patients aged under 70 received more intensive therapies than those aged over 70 (P<0.001). Later, advanced analysis in therapeutic factors was conducted between the patients aged under 70 and those over 70. In the patients aged under 70, significant differences in 4-year overall survival (OS) were noted between UFUR (oral tegafur-uracil plus leucovorin) groups and FOLFOX (5-FU plus oxaliplatin) [65.6% versus (vs) 89.8%, relative risk (RR) 3.780, 95% confidence interval (CI) 1.263-11.315, P = 0.017]. There were also differences in 4-year OS between these patients with and without oxaliplatin-contained regimens (92.1% vs 83.4%, respectively, RR 0.385, 95% CI 0.157-0.946, P = 0.037). In addition, the patients who received intravenous or combined therapy also had higher 4-year OS than those only received oral regimens (92.1% vs 76.6%, P = 0.077), though the finding did not reach statistical significance. In contrast to the survival benefits of above therapeutic settings for the patients aged under 70, there was less advantage in the old patients when they received intensive therapies or even oxaliplatin-contained regimens. Prolonged cycles of adjuvant therapy resulted in no significant benefit to survival rates regardless of ages.The adequate individualized therapeutic strategy plays an important role for stage III colon cancer. Our findings suggested that benefit of oxaliplatin-contained therapy is limited to patients aged under 70 and oral fluoropyrimidines may be an effective option for old patients. In addition, prolonged adjuvant setting is suggested to be unbeneficial for managing stage III colon cancer.